The Assessment of the Relationship Between ADHD and Posttraumatic Stress Disorder in Child and Adolescent Patients - (:unkn) unknown (SAGE PUBLICATIONS INC, 2019)
Objective: This study examined ADHD comorbidity in child and adolescent patients who diagnosed with posttraumatic stress disorder (PTSD) or obsessive compulsive disorder (OCD). Method: Sixty-eight child and adolescent patients with PTSD and 42 child and adolescent patients with OCD were evaluated for ADHD. The sample included 110 patients who were administered structured clinical interviews based on the Diagnostic and Statistical Manual of Mental Disorders (5th ed.). Results: Results showed that 22.05% patients with PTSD and 59.52% patients with OCD met criteria for ADHD. Conclusion: The results of our study indicate that no meaningful differences were detected in comparisons between PTSD and OCD groups, in having ADHD as comorbidity.
Keywords: ADHD; children; adolescents; trauma; ATTENTION-DEFICIT/HYPERACTIVITY DISORDER; DEFICIT HYPERACTIVITY DISORDER; OBSESSIVE-COMPULSIVE DISORDER; DIFFERENTIAL-DIAGNOSIS; PSYCHIATRIC-DISORDERS; COMORBIDITY; SYMPTOMS; VETERANS; TRAUMA; PTSD